2018
DOI: 10.1128/mcb.00590-17
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Invasion-Promoting Region in Insulin Receptor Substrate 2

Abstract: Although the insulin receptor substrate (IRS) proteins IRS1 and IRS2 share considerable homology and activate common signaling pathways, their contributions to breast cancer are distinct. IRS1 has been implicated in the proliferation and survival of breast tumor cells. In contrast, IRS2 facilitates glycolysis, invasion, and metastasis. To determine the mechanistic basis for IRS2-dependent functions, we investigated unique structural features of IRS2 that are required for invasion. Our studies revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…In previous studies, we and others identified a role for IRS2, but not IRS1, in the regulation of invasion, a property of tumor cells that facilitates the metastatic spread of cells to distant sites in the body. 21 , 52 CSCs have also been implicated in metastatic colonization by supporting the initiation of tumor growth in distant organs. 3 The combined ability of IRS2 to mediate signaling that supports both invasion and CSC function may explain the dominant role of IRS2 in metastatic progression.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we and others identified a role for IRS2, but not IRS1, in the regulation of invasion, a property of tumor cells that facilitates the metastatic spread of cells to distant sites in the body. 21 , 52 CSCs have also been implicated in metastatic colonization by supporting the initiation of tumor growth in distant organs. 3 The combined ability of IRS2 to mediate signaling that supports both invasion and CSC function may explain the dominant role of IRS2 in metastatic progression.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] IRS2 enhances glucose metabolism and promotes migration, invasion, and metastasis in various type of tumors. 16,18,[23][24][25][26] However, it is not well known for clinical outcomes of the IRS2 expression in lung cancer progression, so we focused on IRS2 amplification and conducted various experiments to validate whether IRS2 amplification and/or expression is a therapeutic biomarker in metastatic SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Of the hypoxia signaling, known HIFα-regulated genes include ADM [ 28 ], VEGFA [ 12 , 29 ], PDK3 [ 30 ], LOX [ 31 ], MXI1 [ 32 ], PDK1 [ 33 ], XPNPEP1 [ 34 ], SLC2A1 [ 34 ], IRS2 [ 35 ], and PFKFB3 [ 36 ], which have been shown to promote tumor growth and progression in various types of cancers. Previous reports showed that tumorigenesis is promoted via upregulation of glycolysis by ENO2 [ 37 ], PGK1 [ 38 ], ERO1A [ 39 ], P4HA1 [ 40 ], and IRS2 [ 41 ]. TGFBI is an extracellular matrix related oncogene that can lead to a significant enhancement of glycolysis for invasive tumor phenotype [ 42 ].…”
Section: Resultsmentioning
confidence: 99%